Effects of traditional Chinese medicine combined with modern rehabilitation therapies on motor function in children with cerebral palsy: A systematic review and meta-analysis - Chen, Zhengquan; Huang, Zefan; Li, Xin; Deng, Weiwei; Gao, Miao; Jin, Mengdie; Zhou, Xuan; Du, Qing (Frontiers in Neuroscience, 2023)
Objective. Traditional Chinese Medicine (TCM) has considerable experience in the treatment of cerebral palsy (CP), but little evidence shows the effect of a combination of TCM and modern rehabilitation therapies on CP. This systematic review aims to evaluate the effect of integrated TCM and modern rehabilitation therapies on motor development in children with CP. Methods. We systematically searched five databases up to June 2022, including PubMed, the Cumulative Index to Nursing and Allied Health, Cochrane Library, Embase, and Web of Science. Gross motor function measure (GMFM) and Peabody Development Motor Scales-Ⅱ were the primary outcomes to evaluate motor development. Secondary outcomes included the joint range of motion, the Modified Ashworth Scale (MAS), the Berg balance scale, and Activities of Daily living (ADL). Weighted mean differences (WMD) and 95% confidence intervals (CIs) were used to determine intergroup differences. Results. A total of 2211 participants from 22 trials were enrolled in this study. Among these, 1 study was at a low risk of bias and 7 studies showed a high risk of bias. Significant improvements were found in GMFM-66 (WMD 9.33; 95%CI 0.14 to 18.52, P < 0.05, I2 = 92.1%), GMFM-88 (WMD 8.24; 95%CI 3.25 to 13.24, P < 0.01, I2 = 0.0%), Berg balance scale (WMD 4.42; 95%CI 1.21 to 7.63, P < 0.01, I2 = 96.7%) and ADL (WMD 3.78; 95%CI 2.12 to 5.43, P < 0.01, I2 = 58.8%). No adverse events were reported during the TCM intervention in the included studies. The quality of evidence was high to low. Conclusion. Integrated TCM and modern rehabilitation therapies may be an effective and safe intervention protocol to improve gross motor function, muscle tone, and the functional independence of children with CP. However, our results should be interpreted carefully because of the heterogeneity between the included studies.